Health monitoring among refugees: a state-wide, cross-sectional, population-based study in Germany. (13th November 2019) - Biddle, L; Menold, N; Bentner, M; Nöst, S; Jahn, R; Ziegler, S; Bozorgmehr, K
Abstract: Background: Health monitoring in Germany falls short on generating timely, reliable and representative data among migrants, especially transient groups such as asylum seekers and refugees (ASR). We aim to advance health monitoring approaches and obtain reliable estimates on health status and access to health services among ASR in Germany's 3rd largest federal state. Methods: We conducted a state-wide, cross-sectional, population-based health monitoring survey in nine languages among ASR in collective accommodation centres. Questionnaire items capturing health status, access to care and sociodemographic variables were taken from established surveys and translated using a team approach. Random sampling on the level of 1, 938 accommodation centres was employed to draw a balanced sample. Multilingual field teams recruited eligible participants using a "door-to-door" approach. Results: Fieldwork was conducted in 58 centres, obtaining a response rate of 42.2% (n = 412). Age, sex and nationality of the included sample were comparable to the population of asylum applicants in Germany. Adults reported longstanding limitations (16%), bad/very bad general health (19%), pain (25%), chronic illness (40%), and depressive (46%) and anxiety symptoms (45%). 52% utilised primary and 37% specialist care services in the previous 12 months, while reporting unmet needs for primary (31%) and specialist care (32%). Younger and male participants had above-average health status and below-average utilisation, in contrast to older and female ASR. Conclusions: Our health monitoring survey yielded reliable estimates on health status and health care access among ASR, revealing relevant morbidities and patterns of care. Applying rigorous epidemiological methods in linguistically diverse, transient and marginalized populations is challenging, but feasible. Integration of this approach into state- and nation-wide health monitoring strategies is needed to sustain this approach as a health planning tool. Key messages: Applying rigorous epidemiological methods in linguistically diverse, transient and marginalized populations is challenging, but feasible. Sustainable integration of multi-lingual epidemiological methods is required in state- and nation-wide health monitoring to capture health status and access to health services for ASR.